2019
DOI: 10.1186/s12967-019-1909-0
|View full text |Cite
|
Sign up to set email alerts
|

ALS blood expression profiling identifies new biomarkers, patient subgroups, and evidence for neutrophilia and hypoxia

Abstract: Background Amyotrophic lateral sclerosis (ALS) is a debilitating disease with few treatment options. Progress towards new therapies requires validated disease biomarkers, but there is no consensus on which fluid-based measures are most informative. Methods This study analyzed microarray data derived from blood samples of patients with ALS ( n = 396), ALS mimic diseases ( n = 75), and healthy controls ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(77 citation statements)
references
References 149 publications
(268 reference statements)
6
71
0
Order By: Relevance
“…The ratio of neutrophils to monocytes was also shown to be increased (53), as was the total number of granulocytes (54). A micro-array study further confirmed evidence for mild neutrophilia in ALS patients (55). In the SOD1 G93A transgenic mouse ALS model, circulating neutrophils are increased (73), and neutrophils and mast cells are present along peripheral motor axons, with masitinib treatment leading to reduction of axonal damage (56).…”
Section: Abnormalities Of Peripheral Blood Cells Total Leukocyte Counmentioning
confidence: 75%
See 2 more Smart Citations
“…The ratio of neutrophils to monocytes was also shown to be increased (53), as was the total number of granulocytes (54). A micro-array study further confirmed evidence for mild neutrophilia in ALS patients (55). In the SOD1 G93A transgenic mouse ALS model, circulating neutrophils are increased (73), and neutrophils and mast cells are present along peripheral motor axons, with masitinib treatment leading to reduction of axonal damage (56).…”
Section: Abnormalities Of Peripheral Blood Cells Total Leukocyte Counmentioning
confidence: 75%
“…In the peripheral blood monocytes of ALS patients there is also dysregulation of hypoxia pathways (153). A gene expression study found evidence of hypoxia related genes in peripheral blood of ALS patients (55). In an animal model of ALS, hypoxia aggravates the loss of motor neurons (154).…”
Section: Evidence Of Hypoxiamentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting dataset is representative of an early stage breast cancer population and is now available (unadjusted and adjusted) together with patient characteristics and clinical outcomes for future translational research by submitting proposals to the EORTC for access to the gene expression data as well as the clinical and patient data (https://www.eortc.org/data-sharing/), and if granted can be used for analysis and discovery science 31,32 , datamining or creating new signatures of clinically relevant questions 33 .…”
Section: Discussionmentioning
confidence: 99%
“…58,[224][225][226][227] Unfortunately, patients with ALS, at present, have limited therapeutic options (Table 2). 96,173,228 Moreover, given the rapid and terminal progression of the disease postdiagnosis, there is a pressing need to develop new therapies and/or based on mechanism of action repurposing drugs already approved for other diseases. 176,180 Recruiting ALS subjects into traditional clinical trials is challenging because of the low number of cases in the population.…”
Section: Introductionmentioning
confidence: 99%